Effect of a probiotic formulation based on a consortium of actinomycetes on productive performance and intestinal integrity in broilers - Molina M., Daniel (2022)
The effect of a probiotic formula containing a consortium of actinomycetes on the productive performance and intestinal integrity of broiler chickens from 1 to 28 days of age reared in experimental batteries was evaluated. A total of 320 male Cobb 500 chickens were used, randomly distributed in four treatments with eight repetitions and ten chickens per repetition: T1, basal diet (without growth promoters); T2, basal diet + growth promoters (tylosin 200 g/t, salinomycin + nicarbazin 500 g/t); T3, basal diet + Bacillus subtilis (100 g/t); T4, basal diet + actinomycetes consortium (100 g/t). At 21 and 28 days of age, eight birds per treatment were slaughtered to assess intestinal integrity (intestinal histomorphometry) and relative organ weight. At 14 days of age, the actinomycetes consortium significantly improved feed conversion versus the group receiving a basal diet (p<0.05) and had similar performance compared to the other treated groups (p>0.05). There were no statistical differences between the treatments for the productive variables at 7, 21 and 28 days of age (p>0.05). Crypt depth and its relationship with villus length in the duodenum and jejunum were significantly influenced by the administration of the actinomycetes consortium compared to the group that received a basal diet (p<0.05), being statistically similar to the rest of the treated groups (p>0.05) at 21 days of age. The relative weight of the organs was not influenced by the treatments at 21 days of age (p>0.05), while the relative weight of the spleen was statistically lower in the group supplemented with the actinomycetes consortium compared to the group treated with promoters of actinomycetes. growth at 28 days of age (p<0.05). The actinomycetes consortium improved the productive performance and intestinal integrity in a similar way to growth promoters and the commercial probiotic under evaluation, representing an alternative for its effective replacement in the feeding of broilers.